ASSESSMENT OF GENETIC DIVERSITY FOR PHYSICAL AND COOKING QUALITY TRAITS IN RICE (ORYZA SATIVA L.) CULTIVARS USING SIMPLE SEQUENCE REPEATS MARKERS - VIVEK S. NIKAM; B. M. AHER; G. C. JADEJA; G. B. PATIL (The Bioscan, 2014)
Considering the due importance of grain quality in commercial success of the variety, simple sequence repeats (SSRs) were used to find out genetic diversity for physical and cooking quality traits in 31 rice cultivars/ genotypes.Among 31 SSR markers used, 26 SSR marker loci generated polymorphic patterns and a total of 90 alleles were detected. The number of alleles per locus and PIC values ranged from 2-5 with a mean of 3.46 alleles per locus and 0.35(RM2125) to 0.89(RM333) with an average PIC of 0.62, respectively. In clustering pattern Ashoka 200F, AAUDR-1 and GR-9 uplandcoarse grain varieties were grouped together while irrigated varieties GR-11, GR-12, GAR-1, GAR-2, GR-3 and GR-6 exhibited similar clustering pattern.